Stimulation of regeneration by magnetic field in soybean (Glycine max L. Merrill) tissue cultures. - Emiroğlu, Özge; Alikamanoğlu, Sema; Rzakoulieva, Aytekin; ATAK, ÇİMEN (Haliç University, Faculty of Arts and Sciences, Department of Molecular Biology and Genetics, Fındıkzade 34280, İstanbul-Turkey, 2003)
The determination of the effects of magnetic field on tissue cultures will be helpfull for the magnetic field treatments. In this study which was begun with this purpose, the seeds belonging to J 357 soybean variety were used. The soybean seeds were germinated in sterile conditions and cultures were initiated from the shoot tips. The explants in petri dishes were exposed to 2.9-4.6 mT magnetic fields for 2.2, 6.6, and 19.8 seconds periods. Shoot and root formation rate, fresh weights and chlorophyll quantities of regenerated shoots from control and treated explants were determined. While the shoot formation was 61.91% in control group, this rate increased in all magnetic field experiments and this rate raised up to 86.96% and 74.36% respectively in the explants which were exposed to magnetic field at 2.2 and 6.6 seconds periods. Again, while the percentage of root formation in control was 14.29%, this rate raised up to 26.08% and 35.90% respectively in these which were exposed to magnetic field at the same periods. When the fresh weights were determined, the fresh weights of seedlings regenerated from treatment explants from 6.6 seconds significantly increased in accordance with control (P<0.05). Chlorophyll a, chlorophyll b and total chlorophyll quantities of shoot leaf were increased at the treatment magnetic field for 2.2 seconds
Keywords: Soybean; magnetic field; cytokinin; auxin; regeneration